Phage typing and sensitivity test to antibiotics of Salmonella enteritidis isolates from Indonesia - Poernomo, Sri; Priadi, Adin; Natalia, Lily (Indonesian Animal Sciences Society, 2006)
Salmonella enteritidis (SE) is frequently implicated in disease outbreaks such as human food poisoning. Phage typing have been proved to be a valuable and sensitive tool in the control of SE infections. The ability of phage to distinguish varieties among apparently identical serotypes led to the development and acceptance of phage typing as a significant epidemiological procedure. To determine the epidemiological pattern of SE, phage typing of 53 SE isolated from various sources in Indonesia during 1991â1999, has been conducted using 16 typing phages of phage typing scheme of SE obtained from the International Collaborating Center for Enteric Phage typing, Central Public Health Laboratory, Colindale, UK. The lyse blood isosensitest was then used to test the sensitivity of the Salmonella isolates to antibiotics. The phage typing results obtained that of 53 Salmonella isolates there were one S. infantis, one S. berta, and 46 SE phage type 4, 2 SE phage type 7 (from chicken and water), 1 SE phage type 6 (from chicken) and 2 SE phage type 1 (from chicken). SE phage type 4 isolates comprised of 2 isolates from human, 19 isolates from chicken (young and adult), 17 isolates from day old chicks, 4 isolates from fluff, 2 isolates from chicken meat, 1 isolate from poultry farm water, 1 isolate from dog organ. These findings indicated that contaminated chicken appeared to be the sources of human and dog for SE infection. The results of sensitivity test of the isolates to antibiotics showed that most of the Salmonella isolates from Indonesia were resistant to the antibiotics tested. Key Words: Salmonella Enteritidis, Phage typing, Sensitivity test, Indonesia, Chicken